Transclival Approach for Resection of a Pontine Cavernous Malformation: 2-Dimensional Operative Video. Issue 4 (11th February 2020) - London, Dennis; Lieberman, Seth; Tanweer, Omar; Pacione, Donato
Abstract: Cerebral cavernous malformations are common vascular anomalies consisting of a cluster of capillaries without intervening brain tissue. 1 A variety of approaches for resection have been undertaken, 2 and a handful of case reports have described the endoscopic, endonasal, transclival approach. 3 We present a case of a 51-yr-old woman with lupus and hepatitis B-associated cirrhosis who presented with diplopia, dysphagia, and ataxia. She had a left abducens nerve palsy and magnetic resonance imaging (MRI) showed a left pontine cavernous malformation. After a repeat hemorrhage, she consented to surgical resection. The lesion appeared to come to the medial pontine pial surface. Tractography indicated a rightward displacement of the left corticospinal tract. Therefore, an endoscopic, transnasal, transclival approach was chosen. A lumbar drain was placed preoperatively. The clivus and ventral petrous bone were drilled using the vidian canal to help identify the anterior genu of the petrous carotid artery. The clival dura was opened, revealing the abducens nerve exiting the ventral pons. The cavernoma was visible on the surface lateral to the nerve. It was removed using blunt dissection and the remaining cavity inspected. The skull base was reconstructed using an abdominal dermal-fat graft and Alloderm covered by a nasoseptal flap. Postoperatively she had transient swallowing difficulty. The lumbar drain was kept open for 5 d. Cerebrospinal fluid (CSF) leak was ruled out using an intrathecal fluorescein injection. She was discharged home, but presented 2 wk postoperatively with aseptic meningitis, which was treated supportively. Postoperative imaging did not show residual cavernoma.